An An Investigation of Lexical Choices in Translation Among EFL Students - Siti Rahmatiya Buyu; Novriyanto Napu; Sri Widyarti Ali (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to (1) identify and describe the characteristics of lexical choices in EFL students’ Indonesian–English translations and (2) investigate the factors influencing students’ lexical choices during the translation process. A qualitative descriptive approach was employed, involving 20 fourth-semester EFL students at Universitas Negeri Gorontalo enrolled in a Translation and Interpreting course. Data were collected through handwritten translations of an argumentative text and semi-structured retrospective interviews with five selected participants. The translation products were analyzed using Baker’s (1992) framework of meaning, comprising propositional, expressive, presupposed, and evoked meaning, while interview data were analyzed using qualitative content analysis. The findings showed that students generally preserved propositional meaning but experienced greater difficulties with expressive, presupposed, and evoked meanings, particularly in conveying evaluative nuances, producing natural collocations, and maintaining appropriate register. Five interconnected factors influenced students’ lexical choices: limited vocabulary mastery, reliance on dictionaries and machine translation, cognitive factors, limited contextual understanding, and register and source language influence. All five interviewed students reported using Google Translate or DeepL, while four out of five did not consider alternative lexical choices. These findings highlight the need for translation instruction that develops collocational awareness, contextual understanding, register awareness, and critical evaluation of machine translation output.